TANTANGAN PELAKSANAAN SITA JAMINAN DALAM PRAKTIK PERADILAN DI INDONESIA SERTA PERLINDUNGAN HUKUM BAGI KREDITUR - Yustia Okta Pradini; Jason Aaron Riado Simanungkalit; Raihan Heryadi; M. Satria Allariksyah; Farahdinny Siswajanthy (JURNAL ILMIAH NUSANTARA, 2024)
Collateral confiscation is a crucial legal tool in order to guarantee certainty of creditors' rights to the receivables they own. However, the implementation of this collateral confiscation often faces various challenges that can slow down its effectiveness. The purpose of this article is to analyze and research the challenges faced in implementing collateral confiscation in Indonesia, as well as to examine and evaluate legal protection efforts for creditors. By using normative juridical research methods and case study analysis, researchers found that the main challenges in implementing collateral confiscation in judicial practice in Indonesia include several aspects, including complex legal procedures, inconsistencies between applicable regulations and how they are implemented in the field, as well as limited resources in judicial institutions. Apart from that, resistance from debtors and third parties is also a significant obstacle. This article also discusses and evaluates the legal protection that exists for creditors, including monitoring mechanisms and sanctions that can be given if violations occur in its implementation.